Пути снижения механических потерь в подшипниках при проектировании энергоэффективных двигателей - Дзенис, Сергей Евгеньевич (НТУ "ХПИ", 2014)
При проектировании серий энергоэффективных двигателей способом повышения энергоэффективности двигателя является снижение всех видов потерь, в том числе механических потерь. В статье выполнен анализ потерь в подшипниках различных конструктивных исполнений и различных производителей, и смазках, описаны способы снижения механических потерь в подшипниках электродвигателей, даны рекомендаций для практического конструирования. Приведены результаты испытаний двигателей с применением рекомендованных подшипников и смазок.

I At designing series of energy-efficient motors, a way to improve energy efficiency motor is to reduce all types of losses, including mechanical losses. These losses amount to quite a significant proportion of permanent loss, which is practically independent of the load. Therefore, reducing mechanical losses is one of the tools for the design of energy-efficient motors. Previously, researchers' attention was paid to the optimization of mechanical losses of high-speed electric motors (exceeding 20 000 rpm). As a means to reduce mechanical losses recommended replacement ball bearing bearings electromagnetic. Analysis was performed on the motor loss interval 63-132, different manufacturing plants of Russia, Ukraine and Belarus. Describes in detail the division averaged losses by types of for motors with 2p = 2, 4, 2p = 6, measured experimentally on the basis of electric motors 80. Since the analytical methods for calculating the mechanical losses in the bearings do not give correct results, this study is based on experimental data.
Ways of decrease mechanical losses in the bearings in the design of energy-efficient motors
Keywords: электродвигатели; асинхронные трехфазные электродвигатели; короткозамкнутый ротор; энергоэффективные электродвигатели; механические потери; подшипники; induction motors; energy-efficient induction motors; mechanical bearings losses; losses in grease